Mediating marginality : mounds, pots and performances at the Bronze Age Cemetery of Purić-Ljubanj, eastern Croatia - Budden-Hoskins, Sandy, (Archaeopress Archaeology, 2022)
This study draws on eight years of excavation and survey at the newly discovered Bronze Age Cemetery of Puric-Ljubanj in the county of Vukovar-Syrmia in eastern Croatia.